Resin composition for laser direct structuring, molded article, and method for manufacturing plated molded article

JP7632297B2Active Publication Date: 2025-02-19MITSUBISHI CHEM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021554946
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-06
Filing Date
2020-11-04
Publication Date
2025-02-19
Estimated Expiration
2040-11-04

AI Technical Summary

Benefits of technology

【0007】 本発明により、成形品にメッキを形成でき、かつ、低誘電正接のレーザーダイレクトストラクチャリング用樹脂組成物、ならびに、成形品、および、メッキ付き成形品の製造方法を提供可能になった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632297000016
    Figure 0007632297000016
  • Figure 0007632297000001
    Figure 0007632297000001
  • Figure 0007632297000002
    Figure 0007632297000002
Patent Text Reader

Abstract

A resin composition for laser direct structuring, which has a low loss tangent and on which plating can be formed, a molded product, and a production method of a plated molded product are provided. This resin composition for laser direct structuring contains a polycarbonate resin and a laser direct structuring additive, wherein at least 5 mass% of all constituent units of the polycarbonate resin are represented by formula (1). In formula (1), R1 and R2 are independently a hydrogen atom or a methyl group, and W1 represents a single bond or a divalent group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for laser direct structuring, a molded article, and a method for producing a plated molded article, and more particularly to an electronic / electrical device part that uses electromagnetic waves with a frequency of 1 GHz or more. [Background technology]

[0002] In recent years, with the development of mobile phones including smartphones, various methods for manufacturing antennas inside mobile phones have been considered. In particular, there is a demand for a method for manufacturing an antenna that can be designed three-dimensionally for a mobile phone. As one of the techniques for forming such a three-dimensional antenna, laser direct structuring (hereinafter, in this specification, sometimes referred to as "LDS") technology has attracted attention. The LDS technology is, for example, a technology for irradiating a laser onto the surface of a resin molded product containing an LDS additive to activate it, and applying a metal to the activated part to form a plating. The feature of this technology is that a metal structure such as an antenna can be directly manufactured on the surface of a resin molded product without using an adhesive or the like. Such LDS technology is disclosed, for example, in Patent Documents 1 to 4. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2000-503817 [Patent Document 2] Special Publication No. 2004-534408 [Patent Document 3] International Publication No. 2009 / 141800 [Patent Document 4] International Publication No. 2012 / 128219 Summary of the Invention [Problem to be solved by the invention]

[0004] When a metal structure such as an antenna is directly formed on the surface of a resin molded article, the resin molded article is sometimes required to have a low dielectric tangent depending on the application. The present invention aims to solve these problems, and to provide a resin composition capable of forming a plating and having a low dielectric tangent, as well as a molded article and a method for manufacturing a plated molded article. [Means for solving the problem]

[0005] In view of the above-mentioned problems, the present inventors have conducted research and found that by using a polycarbonate resin containing a specific carbonate unit, it is possible to obtain a resin composition having a low dielectric tangent while maintaining plating properties. Specifically, the above-mentioned problems have been solved by the following means. <1> Contains polycarbonate resin and laser direct structuring additives. A resin composition for laser direct structuring, wherein 5% by mass or more of all structural units of the polycarbonate resin are structural units represented by formula (1). [ka] (In formula (1), R 1 and R 2 are each independently a hydrogen atom or a methyl group; W 1 represents a single bond or a divalent group. <2> The laser direct structuring additive is contained in an amount of 0.1 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the polycarbonate resin. <1> The resin composition according to claim 1. <3> Further, the composition contains an inorganic filler in an amount of 10 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the polycarbonate resin. <1> or <2> The resin composition according to claim 1. <4> The mass ratio of the structural unit represented by formula (1) in the polycarbonate resin relative to 100 parts by mass of the inorganic filler is 150 parts by mass or more. <3> The resin composition according to claim 1. <5> The inorganic filler includes at least one selected from the group consisting of glass, talc, wollastonite, titanium oxide, and boron nitride. <3> or <4> The resin composition according to claim 1. <6> The inorganic filler includes glass fibers. <3> or <4> The resin composition according to claim 1. <7> Furthermore, the polycarbonate resin contains a structural unit represented by formula (5): <1> ~ <6> 10. The resin composition according to claim 9 . [ka] (In formula (5), W 2 represents a single bond or a divalent group. <8> a polycarbonate resin (A1) in which 90 mass% or more of all structural units are structural units represented by the formula (1) and a polycarbonate resin (A2) in which 90 mass% or more of all structural units are structural units represented by the formula (5), and 25 mass% or more of the polycarbonate resin contained in the resin composition is the polycarbonate resin (A1); <7> The resin composition according to claim 1. <9> The viscosity average molecular weight of the polycarbonate resin (A1) is 16,000 or more and 30,000 or less, and the viscosity average molecular weight of the polycarbonate resin (A2) is 16,000 or more and 35,000 or less. <8> The resin composition according to claim 1. <10> Further, the impact resistance improver is contained in an amount of 2 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the polycarbonate resin. <1> ~ <9> 10. The resin composition according to claim 9 . <11> When the resin composition is molded into a flat plate, the pencil hardness measured according to JIS K5600 is H or more. <1> ~ <10> 10. The resin composition according to claim 9 . <12> When the resin composition is molded into a flat plate, the dielectric tangent at a frequency of 2.45 GHz is 0.0200 or less. <1> ~ <11> 10. The resin composition according to claim 9 . <13> The laser direct structuring additive comprises copper chromium oxide, an oxide containing at least one of antimony and phosphorus and tin, and at least two metals, and has a resistivity of 5×103 At least one selected from the group consisting of conductive oxides with a conductivity of Ω·cm or less; <1> ~ <12> 10. The resin composition according to claim 9 . <14> The laser direct structuring additive comprises at least two metals and has a resistivity of 5×10 3 At least one selected from the group consisting of conductive oxides with a conductivity of Ω·cm or less; <1> ~ <12> 10. The resin composition according to claim 9 . <15> The proportion of the structural unit represented by formula (1) to the total structural units of the polycarbonate resin is 30 to 60 mass%. <1> ~ <14> 10. The resin composition according to claim 9 . <16> The content of the laser direct structuring additive relative to 100 parts by mass of the polycarbonate resin is 30 parts by mass or more and 150 parts by mass or less. <1> ~ <15> 10. The resin composition according to claim 9 . <17> For electronic and electrical equipment parts that use electromagnetic waves with frequencies of 1 GHz or higher. <1> ~ <16> 10. The resin composition according to claim 9 . <18> <1> ~ <17> 2. A molded article formed from the resin composition according to claim 1. <19> The molded article is an electronic or electrical device part that uses electromagnetic waves with a frequency of 1 GHz or more. <18> The molded article according to claim 1. <20> The molded article has a plating on its surface. <18> or <19> The molded article according to claim 1. <21> The plating has antenna properties. <20> The molded article according to claim 1. <22> <1> ~ <17> irradiating a surface of a molded article formed from the resin composition according to any one of claims 1 to 5 with a laser, and then applying a metal to form a plating.

[0006] Furthermore, in any of the above resin compositions, in formula (1), W 1 The resin composition is represented by formula (2a) described below. Further, in any one of the above resin compositions, the constitutional unit represented by formula (1) is a resin composition represented by formula (3) described below. <c>Furthermore, in any of the above resin compositions, the carbonate unit other than the structural unit represented by formula (1) is a structural unit represented by formula (5) described below, W 2 The resin composition is represented by formula (2a) described below. <d>Further, in any of the above resin compositions, the total amount of the polycarbonate resin (A1) and the polycarbonate resin (A2) accounts for 90 mass % or more of the polycarbonate resin contained in the resin composition. <e>Further, any of the above resin compositions does not contain an inorganic filler, and contains a polycarbonate resin in a proportion of 80 mass % or more in the resin composition. <f>Further, any one of the above resin compositions further comprises an inorganic filler, and the total content of the polycarbonate resin and the inorganic filler in the resin composition is 80 mass % or more. <g>Further, any one of the above resin compositions may contain an inorganic filler, and the inorganic filler may be fibrous. <h>Further, in any of the above resin compositions, the resin composition further comprises a heat stabilizer (preferably a phosphorus-based stabilizer, more preferably tridecyl phosphite) in a ratio of 0.001 part by mass or more and 1 part by mass or less per 100 parts by mass of the polycarbonate resin. Further, in any of the above resin compositions, the resin composition contains an antioxidant (preferably a hindered phenol-based antioxidant, more preferably octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) in a ratio of 0.001 part by mass or more and 1 part by mass or less per 100 parts by mass of the polycarbonate resin. <j>Further, in any of the above resin compositions, the resin composition contains a release agent (preferably an ester of an aliphatic carboxylic acid and an alcohol, more preferably pentaerythritol tetrastearate) in a ratio of 0.001 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the polycarbonate resin. <k>Further, in any of the above resin compositions, the resin composition contains an elastomer (preferably a graft copolymer in which a (meth)acrylic acid ester compound is graft polymerized onto a rubber component, more preferably a methyl methacrylate-butadiene copolymer which is a core / shell type graft copolymer) as an impact resistance improver in a ratio of 2 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the polycarbonate resin. <l>Further, in any of the above resin compositions, the total content of the polycarbonate resin, the LDS additive, the inorganic filler, and the heat stabilizer, the antioxidant, the release agent, and the elastomer which are selectively blended is 98 mass% or more (preferably 100 mass%). <m>Furthermore, in any of the above resin compositions, the LDS additive contains an oxide containing antimony and tin, and at least two kinds of metals, and has a resistivity of 5×10 3 A resin composition comprising at least one conductive oxide having a resistivity of Ω·cm or less selected from the group consisting of conductive oxides containing metals in Group n (n is an integer from 3 to 16) and Group n+1 metals in the periodic table. Effect of the Invention

[0007] INDUSTRIAL APPLICABILITY The present invention makes it possible to provide a resin composition for laser direct structuring that is capable of forming plating on a molded article and has a low dielectric tangent, as well as a molded article and a method for producing a plated molded article. [Brief description of the drawings]

[0008] < / m> < / l> < / k> < / j> < / h> < / g> < / f> < / e> < / d> < / c> [Figure 1] FIG. 2 is a schematic diagram showing a process of plating the surface of a molded product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below. In this specification, the word "to" is used to mean that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified. In this specification, "parts by mass" indicates the relative amount of a component, and "% by mass" indicates the absolute amount of a component.

[0010] The resin composition for laser direct structuring of the present invention (hereinafter, simply referred to as the "resin composition") contains a polycarbonate resin and a laser direct structuring additive, and is characterized in that 5 mass% or more of the total structural units of the polycarbonate resin are structural units represented by formula (1). By adopting such a constitution, it is possible to form a plating on the molded article, achieve a low dielectric tangent, and further increase the surface hardness of the obtained molded article. The reason for this is presumably due to the fact that the polycarbonate resin contains a certain proportion or more of a structural unit represented by formula (1), such as a structural unit derived from bisphenol C.

[0011] <Polycarbonate resin> The resin composition of the present invention contains a polycarbonate resin, in which 5% by mass or more of all the constituent units are the constituent units represented by formula (1).

[0012] In the polycarbonate resin used in the present invention, the proportion of the structural unit represented by formula (1) in all structural units is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, even more preferably 30% by mass or more, and may be 35% by mass or more. The upper limit of the proportion of the structural unit represented by formula (1) in all structural units may be 100% by mass, but is preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, even more preferably 65% ​​by mass or less, and may be 60% by mass or less, 55% by mass or less, or less than 50% by mass. The polycarbonate resin may contain only one type of constitutional unit represented by formula (1), or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0013] The polycarbonate resin used in the present invention is usually composed of a structural unit represented by formula (1), carbonate units other than the structural unit represented by formula (1) (hereinafter sometimes referred to as "other carbonate units"), and a terminal group. The other carbonate units may have a branched structure. In the present invention, the content of the structural unit represented by formula (1) and other carbonate units is based on all structural units excluding terminal groups (100 mass %). In the present invention, when other carbonate units are contained, only one type may be contained, or two or more types may be contained. When two or more types are contained, it is preferable that the total amount is within the above range.

[0014] Next, the constitutional unit represented by formula (1) will be described. The constitutional unit represented by formula (1) is as follows. [ka] (In formula (1), R 1 and R 2 are each independently a hydrogen atom or a methyl group; W 1 represents a single bond or a divalent group.

[0015] In formula (1), R 1 and R 2 R represents a hydrogen atom or a methyl group. 1 and R 2 However, when it is a hydrogen atom, the weather resistance of the molded article of the present invention tends to be improved. 1 and R 2 However, in the case of a methyl group, the heat resistance and the moisture and heat resistance stability of the molded article of the present invention tend to be further improved. 1 and R 2 may be appropriately selected depending on requirements, but is preferably a hydrogen atom.

[0016] In formula (1), W 1 represents a single bond or a divalent group. Examples of the divalent group include an oxygen atom, a sulfur atom, a divalent organic group, and a group formed from a combination of these, and a divalent organic group is preferable. The divalent organic group is not particularly limited and can be appropriately selected and used as long as it is a conventionally known group, and examples thereof include organic groups represented by the following formulae (2a) to (2h).

[0017] [ka]

[0018] In formula (2a), R 3 and R 4 each independently represents a hydrogen atom, a monovalent hydrocarbon group having 1 to 24 carbon atoms, or an alkoxy group having 1 to 24 carbon atoms, and is preferably a monovalent hydrocarbon group having 1 to 24 carbon atoms.

[0019] Examples of the monovalent hydrocarbon group having 1 to 24 carbon atoms include an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, an aryl group having 6 to 24 carbon atoms which may have a substituent, and an arylalkyl group having 7 to 24 carbon atoms, and the like. An alkyl group having 1 to 24 carbon atoms is preferred.

[0020] Examples of the alkyl group having 1 to 24 carbon atoms include linear and branched alkyl groups and alkyl groups having a partial cyclic structure, among which linear alkyl groups are preferred. Examples of the alkyl group having 1 to 24 carbon atoms include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, and n-octyl groups, among which methyl is preferred.

[0021] Examples of the alkenyl group having 2 to 24 carbon atoms include linear and branched alkenyl groups and alkenyl groups having a partial cyclic structure, with linear alkenyl groups being preferred. Examples of the linear alkenyl group having 2 to 24 carbon atoms include vinyl, n-propenyl, n-butenyl, n-pentenyl, n-hexenyl, n-heptenyl, and n-octenyl groups, with vinyl being preferred.

[0022] Examples of the aryl group having 6 to 24 carbon atoms include aryl groups which may have a substituent such as an alkyl group, such as a phenyl group, a naphthyl group, a methylphenyl group, a dimethylphenyl group, a trimethylphenyl group, etc. Examples of the arylalkyl group having 7 to 24 carbon atoms include a benzyl group, etc.

[0023] Examples of the alkoxy group having 1 to 24 carbon atoms include linear, branched, and partially cyclic alkoxy groups, with linear alkoxy groups being preferred. Specific examples of linear alkoxy groups include methoxy, ethoxy, propoxy, and butoxy.

[0024] In formula (2b), X 1 is an oxygen atom or NR a Here, R a is the above R 3 and R 4 is synonymous with.

[0025] In formula (2c), X 2 represents a divalent hydrocarbon group having 3 to 18 carbon atoms, such as a propylene group, butylene group, pentylene group, hexylene group, heptylene group, octylene group, nonylene group, decylene group, undecylene group, and dodecynylene group, each of which may further have a substituent. Examples of the substituent include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a phenyl group. Furthermore, X 2 may have a crosslinked structure. Formula (2c) is preferably represented by formula (2i). [ka]

[0026] In formula (2i), R 11 each independently represents a monovalent hydrocarbon group having 1 to 24 carbon atoms or an alkoxy group having 1 to 24 carbon atoms. For details of the monovalent hydrocarbon group having 1 to 24 carbon atoms and the alkoxy group having 1 to 24 carbon atoms, see R 3 is the same as: q is an integer of 0 to 3, with 0 being preferred. * indicates the site of attachment to other groups.

[0027] In formula (2h), X 3 represents an alkylene group having 1 to 7 carbon atoms. This alkylene group may be linear or branched, and may have a cyclic structure, and examples thereof include a methylene group, an ethylene group, a propylene group, and a butylene group.

[0028] m represents an integer of 1 to 500, preferably 5 to 300, and more preferably 10 to 100.

[0029] Specific examples of raw material monomers for the constitutional unit represented by formula (1) include, for example, Bis(4-hydroxy-3-methylphenyl)methane, Bis(4-hydroxy-3,5-dimethylphenyl)methane, 1,1-bis(4-hydroxy-3-methylphenyl)ethane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)ethane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)butane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)butane, 1,3-bis(2-(4-hydroxy-3-methylphenyl)-2-propyl)benzene, 1,4-bis(2-(4-hydroxy-3-methylphenyl)-2-propyl)benzene, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)cyclohexane, 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxy-3,5-dimethylphenyl)-3,3,5-trimethylcyclohexane, Bis(4-hydroxy-3-methylphenyl)diphenylmethane, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-hydroxy-3,5-dimethylphenyl)fluorene, bis(4-hydroxy-3-methylphenyl)sulfone, 3,3-bis(4-hydroxy-3-methylphenyl)phthalide, 2-methyl-3,3'-bis(4-hydroxy-3-methylphenyl)phthalimidine, 2-phenyl-3,3'-bis(4-hydroxy-3-methylphenyl)phthalimidine, 4,4'-dihydroxy-3,3'-dimethylbiphenyl, 4,4'-Dihydroxy-3,3',5,5'-tetramethylbiphenyl Examples of structural units include those derived from aromatic dihydroxy compounds such as the above.

[0030] As the aromatic dihydroxy compound, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 1,1-bis(4-hydroxy-3-methylphenyl)cyclohexane, and 1,1-bis(4-hydroxy-3-methylphenyl)-3,3,5-trimethylcyclohexane are preferred, 2,2-bis(4-hydroxy-3-methylphenyl)propane and 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane are more preferred, and 2,2-bis(4-hydroxy-3-methylphenyl)propane is even more preferred.

[0031] That is, the structural unit represented by formula (1) is preferably a structural unit represented by the following formula (3), formula (4), or formula (4-2), more preferably a structural unit represented by formula (3) or formula (4-2), and even more preferably a structural unit represented by formula (3). By including these structural units, the effects of the present invention are more effectively exhibited.

[0032] [ka] [ka]

[0033] Next, carbonate units other than the structural unit represented by formula (1) will be described. The other carbonate units contained in the polycarbonate resin of the present invention are not particularly limited in terms of type, etc., and a wide variety of known carbonate units can be used.

[0034] Specific examples of the other carbonate units include the structural units represented by the following formulae (5) and (6), and the structural unit represented by formula (5) is preferred. In particular, it is preferred that 90% by mass or more (preferably 95% by mass or more, more preferably 99% by mass or more) of the other carbonate units are structural units represented by formula (5).

[0035] [ka]

[0036] In formula (5), W 2 is the aforementioned W 1 The same definition and preferred range are also applicable. In particular, the formula (2a) is preferred.

[0037] [ka]

[0038] In formula (6), R 5 , R 6 , R 7 , R 8 , R 9 and R 10 Each independently represents at least one selected from a hydrogen atom and an alkyl group having 1 to 6 carbon atoms. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, and a propyl group. In formula (6), R 5 , R 6 , R 7 , and R 8 R is preferably an alkyl group having 1 to 6 carbon atoms, and more preferably a methyl group. 9 and R 10 is preferably a hydrogen atom.

[0039] Other carbonate units include, specifically, structural units derived from 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 2,2-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, and 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane. Among them, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) and 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane are more preferred, and 2,2-bis(4-hydroxyphenyl)propane (bisphenol A) is even more preferred.

[0040] Next, specific examples of the polycarbonate resin in the present invention will be described. In the present invention, the following polycarbonate resins are preferred. (1) A blend of polycarbonate resin (A1) and polycarbonate resin (A2) (2) Polycarbonate resin (A3) (3) A blend of polycarbonate resin (A1) and polycarbonate resin (A3) (4) A blend of polycarbonate resin (A2) and polycarbonate resin (A3) (5) A blend of polycarbonate resin (A1), polycarbonate resin (A2) and polycarbonate resin (A3) (6) In the above (1) to (5), a blend further containing a polycarbonate resin other than the polycarbonate resin (A1) to the polycarbonate resin (A3) in a proportion of more than 0 mass% and not more than 5 mass%.

[0041] Here, the polycarbonate resin (A1) to the polycarbonate resin (A3) are as follows. Polycarbonate resin (A1): A polycarbonate resin in which 90% by mass or more (preferably 95% by mass or more, more preferably 99% by mass or more) of all structural units are structural units represented by formula (1). Polycarbonate resin (A2): A polycarbonate resin in which 90% by mass or more (preferably 95% by mass or more, more preferably 99% by mass or more) of all structural units are structural units represented by formula (5). Polycarbonate resin (A3): A polycarbonate resin in which 1 to 99% by mass of all structural units are structural units represented by formula (1) and 99 to 1% by mass of all structural units are structural units represented by formula (5).

[0042] A first embodiment of the polycarbonate resin in the present invention is an embodiment that contains a polycarbonate resin (A1) and a polycarbonate resin (A2), and 25 mass % or more of the polycarbonate resin contained in the resin composition is the polycarbonate resin (A1). In the first embodiment, the proportion of the polycarbonate resin (A1) in the polycarbonate resin contained in the resin composition is preferably 28% by mass or more, more preferably 30% by mass or more. By making it equal to or more than the lower limit, the dielectric loss tangent tends to be lower and the surface hardness tends to be improved. In the first embodiment, the proportion of the polycarbonate resin (A1) in the polycarbonate resin contained in the resin composition is preferably 100% by mass or less, more preferably 75% by mass or less, even more preferably 65% ​​by mass or less, and even more preferably 60% by mass or less. By making it equal to or less than the upper limit, mechanical properties such as heat resistance and strength required for electronic and electric device housings tend to be further improved. In the first embodiment, the total amount of the polycarbonate resin (A1) and the polycarbonate resin (A2) preferably accounts for 90 mass% or more of the polycarbonate resin contained in the resin composition, more preferably accounts for 95 mass% or more, and even more preferably accounts for 99 mass% or more, and may be 100 mass%.

[0043] A second embodiment of the polycarbonate resin in the present invention is an embodiment in which the polycarbonate resin contains a polycarbonate resin (A3) in which 1 to 99 mass% of all structural units are structural units represented by formula (1) and 99 to 1 mass% of all structural units are structural units represented by formula (5), and 40 mass% or more, preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 70 mass% or more, still more preferably 80 mass% or more, even more preferably 90 mass% or more, and still more preferably 99 mass% or more of the polycarbonate resin contained in the resin composition is the polycarbonate resin (A3).

[0044] In the second embodiment, the ratio of the structural unit represented by formula (1) in the polycarbonate resin (A3) is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, and even more preferably 50% by mass or more. By making it equal to or more than the lower limit, the dielectric tangent tends to be lower and the pencil hardness tends to be improved. In addition, the ratio of the structural unit represented by formula (1) in the polycarbonate resin (A3) is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, even more preferably 70% by mass or less, and even more preferably 60% by mass or less. By making it equal to or less than the upper limit, the durability required for electronic and electrical equipment parts and the like tends to be improved.

[0045] In the second embodiment, the ratio of the structural unit represented by formula (5) in the polycarbonate resin (A3) is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, and even more preferably 50% by mass or more. By making it equal to or more than the lower limit, the dielectric tangent tends to be lower and the pencil hardness tends to be improved. In addition, the ratio of the structural unit represented by formula (1) in the polycarbonate resin (A3) is preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 80% by mass or less, even more preferably 70% by mass or less, and even more preferably 60% by mass or less. By making it equal to or less than the upper limit, the durability required for electronic and electrical equipment parts and the like tends to be improved.

[0046] The viscosity average molecular weight of the polycarbonate resin contained in the resin composition of the present invention (in the case of a mixture, the viscosity average molecular weight of the mixture) is not particularly limited and can be appropriately selected as long as it does not impair the object of the present invention, and is usually 10,000 to 50,000 in terms of viscosity average molecular weight (Mv) calculated from the solution viscosity. The viscosity average molecular weight (Mv) of the polycarbonate resin is preferably 11,000 or more, more preferably 12,000 or more, even more preferably 13,000 or more, and particularly preferably 14,000 or more. The viscosity average molecular weight (Mv) of the polycarbonate resin is preferably 40,000 or less, more preferably 35,000 or less, even more preferably 30,000 or less, and particularly preferably 28,000 or less.

[0047] In the present invention, the viscosity average molecular weight of the polycarbonate resin (A1) is preferably 16,000 or more and 30,000 or less. The viscosity average molecular weight of the polycarbonate resin (A1) is preferably 17,000 or more and is preferably 28,000 or less, and more preferably 26,000 or less.

[0048] The viscosity average molecular weight of the polycarbonate resin (A2) is preferably 16,000 or more and 35,000 or less. The viscosity average molecular weight of the polycarbonate resin (A2) is preferably 18,000 or more, and more preferably 20,000 or more. The viscosity average molecular weight of the polycarbonate resin (A1) is more preferably 30,000 or less, and even more preferably 27,000 or less. In the present invention, particularly in the first embodiment of the polycarbonate resin, it is preferred that the polycarbonate resins (A1) and (A2) satisfy the above viscosity average molecular weight.

[0049] Furthermore, the viscosity average molecular weight of the polycarbonate resin (A3) is preferably 10,000 or more, and more preferably 15,000 or more. Also, the viscosity average molecular weight of the polycarbonate resin (A3) is preferably 35,000 or less, more preferably 30,000 or less, even more preferably 26,000 or less, and even more preferably 24,000 or less. In the present invention, it is particularly preferable for the polycarbonate resin in the second embodiment to satisfy the above viscosity average molecular weight.

[0050] The viscosity average molecular weight is measured according to the description in the Examples section below.

[0051] The method for producing polycarbonate resin is not particularly limited and can be appropriately selected and used as long as it is a known method.The method for producing polycarbonate resin can be, for example, melt transesterification method, interfacial polymerization method, pyridine method, ring-opening polymerization method of cyclic carbonate compound, solid-phase transesterification method of prepolymer, etc., among which, melt transesterification method and interfacial polymerization method are preferred, and melt transesterification method is more preferred.

[0052] When the resin composition of the present invention does not contain an inorganic filler, it preferably contains the polycarbonate resin and the LDS additive in a total amount of 80 mass % or more, more preferably 85 mass % or more, even more preferably 90 mass % or more, even more preferably 95 mass % or more, and may contain 98 mass % or more. Furthermore, when the resin composition of the present invention contains an inorganic filler, it preferably contains the polycarbonate resin, the LDS additive, and the inorganic filler in a total amount of 80 mass % or more, more preferably 85 mass % or more, even more preferably 90 mass % or more, even more preferably 95 mass % or more, and may contain 98 mass % or more. Furthermore, in the resin composition of the present invention, the total amount of the LDS additive and the inorganic filler to be blended as required is preferably 15 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 60 parts by mass or more, even more preferably 70 parts by mass or more, even more preferably 100 parts by mass or more, particularly preferably 120 parts by mass or more, and most preferably 140 parts by mass or more, relative to 100 parts by mass of the polycarbonate resin. By making it equal to or more than the lower limit, both the high dielectric constant and the low dielectric loss tangent tend to be improved in a well-balanced manner. Furthermore, the total amount of the LDS additive and the inorganic filler to be blended as required relative to 100 parts by mass of the polycarbonate resin is preferably 200 parts by mass or less, more preferably 180 parts by mass or less, and even more preferably 160 parts by mass or less. By making it equal to or less than the upper limit, both the strength and LDS performance required for electronic and electrical equipment parts can be improved in a well-balanced manner. The polycarbonate resin may be one kind or two or more kinds. When two or more kinds are contained, the total amount is preferably within the above range.

[0053] <Laser direct structuring additive> The resin composition of the present invention includes a laser direct structuring (LDS) additive. The LDS additive in the present invention refers to a compound that can form a plate when 10 parts by mass of an additive considered to be an LDS additive is added to 100 parts by mass of polycarbonate resin, irradiated with a YAG laser having a wavelength of 1064 nm at an output of 10 W, a frequency of 80 kHz, and a speed of 3 m / s, and then the plating process is performed in an electroless plating tank of M-Copper 85 manufactured by MacDermid, and a metal is applied to the laser irradiated surface. The LDS additive used in the present invention may be a synthetic product or a commercially available product. In addition to those commercially available as LDS additives, commercially available products may be substances sold for other purposes as long as they satisfy the requirements of the LDS additive in the present invention. Only one type of LDS additive may be used, or two or more types may be used in combination.

[0054] A first embodiment of the LDS additive used in the present invention is copper chromium oxide. The LDS additive of the first embodiment preferably contains 10 to 30 mass % of copper and 15 to 50 mass % of chromium.

[0055] The copper chromium oxide preferably has a spinel structure, which is one of the typical crystal structures found in AB2O4 type compounds (A and B are metal elements) in double oxides.

[0056] The LDS additive (copper chromium oxide) of the first embodiment may contain trace amounts of other metals. Examples of other metals include antimony, tin, lead, indium, iron, cobalt, nickel, zinc, cadmium, silver, bismuth, arsenic, manganese, magnesium, and calcium, with manganese being preferred. These metals may be present as oxides. A preferred example of the LDS additive of the first embodiment is an LDS additive having a content of metal oxides other than copper chromium oxide of 10 mass % or less.

[0057] A second embodiment of the LDS additive used in the present invention is an oxide containing at least one of antimony and phosphorus and tin, and is preferably a metal oxide containing antimony and tin.

[0058] The LDS additive of the second embodiment preferably has a tin content greater than the phosphorus and antimony contents, and more preferably the amount of tin relative to the total amount of tin, phosphorus, and antimony is 80 mass % or more.

[0059] In particular, as the LDS additive of the second embodiment, a metal oxide in which the amount of tin relative to the total amount of tin and antimony is 80 mass % or more is more preferable.

[0060] More specifically, the LDS additive of the second embodiment includes antimony-doped tin oxide, antimony oxide-doped tin oxide, phosphorus-doped tin oxide, and phosphorus oxide-doped tin oxide, with antimony oxide-doped tin oxide and antimony oxide-doped tin oxide being preferred, and antimony oxide-doped tin oxide being more preferred.

[0061] A third embodiment of the LDS additive used in the present invention comprises at least two metals and has a resistivity of 5×10 3 The conductive oxide has a resistivity of 8×10 or less. By using the LDS additive of the third embodiment, the dielectric constant and the dielectric loss tangent tend to be improved in a well-balanced manner. 2 Ω cm or less is preferable, and 7×10 2 Ω cm or less is more preferable, and 5×10 2 It is more preferable that the resistivity is Ω·cm or less. There is no particular lower limit, but for example, 1×10 1 It may be Ω·cm or more, and even 1×10 2 It may be Ω·cm or more. The resistivity of the conductive oxide in the present invention generally refers to powder resistivity, and is 100 kgf / cm when 10 g of fine powder of the conductive oxide is placed in a cylinder with an inner diameter of 25 mm and the inside surface of which is coated with Teflon (registered trademark). 2 (filling rate 20%) and measuring it using a Yokogawa Electric Corporation "3223" tester.

[0062] The LDS additive used in the third embodiment has a resistivity of 5×10 3 There are no particular limitations as long as the LDS additive contains a conductive oxide with a resistivity of Ω·cm or less, but it preferably contains at least two metals, and more preferably contains a metal in group n (n is an integer from 3 to 16) and a metal in group n+1 of the periodic table. n is more preferably an integer from 10 to 13, and even more preferably 12 or 13. That is, an example of the LDS additive used in the third embodiment contains aluminum and zinc and has a resistivity of 5×10 3 It is a conductive oxide with a conductivity of less than Ω·cm. In the LDS additive used in the third embodiment, when the total content of the metal of group n (n is an integer of 3 to 16) of the periodic table and the metal of group n+1 in the LDS additive is taken as 100 mol%, the content of one metal is preferably 15 mol% or less, more preferably 12 mol% or less, and even more preferably 10 mol% or less. There is no particular restriction on the lower limit, but 0.0001 mol% or more is preferable. By setting the content of two or more metals within such a range, plating properties can be improved. In the present invention, an oxide of a metal of group n doped with a metal of group n+1 is particularly preferable. Furthermore, the LDS additive used in the third embodiment preferably contains metal components in the LDS additive of 98 mass % or more, the metals being composed of metals in Group n and Group n+1 of the periodic table.

[0063] Examples of metals in the n-group of the periodic table include metals in the 3rd group (scandium, yttrium), 4th group (titanium, zirconium, etc.), 5th group (vanadium, niobium, etc.), 6th group (chromium, molybdenum, etc.), 7th group (manganese, etc.), 8th group (iron, ruthenium, etc.), 9th group (cobalt, rhodium, iridium, etc.), 10th group (nickel, palladium, platinum), 11th group (copper, silver, gold, etc.), 12th group (zinc, cadmium, etc.), 13th group (aluminum, gallium, indium, etc.), 14th group (germanium, tin, etc.), 15th group (arsenic, antimony, etc.), and 16th group (selenium, tellurium, etc.). Among them, metals in the 12th group (n=12) are preferred, and zinc is more preferred.

[0064] Examples of metals in the n+1 group of the periodic table include metals in the 4th group (titanium, zirconium, etc.), 5th group (vanadium, niobium, etc.), 6th group (chromium, molybdenum, etc.), 7th group (manganese, etc.), 8th group (iron, ruthenium, etc.), 9th group (cobalt, rhodium, iridium, etc.), 10th group (nickel, palladium, platinum), 11th group (copper, silver, gold, etc.), 12th group (zinc, cadmium, etc.), 13th group (aluminum, gallium, indium, etc.), 14th group (germanium, tin, etc.), 15th group (arsenic, antimony, etc.), and 16th group (selenium, tellurium, etc.). Among them, metals in the 13th group (n+1=13) are preferred, aluminum or gallium is more preferred, and aluminum is even more preferred.

[0065] The LDS additive used in the third embodiment is preferably aluminum doped zinc oxide. Furthermore, the LDS additive used in the third embodiment may contain a metal other than the conductive metal oxide. Examples of metals other than the conductive oxide include antimony, titanium, indium, iron, cobalt, nickel, cadmium, silver, bismuth, arsenic, manganese, chromium, magnesium, and calcium. These metals may exist as oxides. The content of these metals is preferably 0.01% by mass or less relative to the LDS additive.

[0066] The resin composition of the present invention preferably contains the laser direct structuring additive in a range of 0.1 parts by mass or more and 150 parts by mass or less relative to 100 parts by mass of the polycarbonate resin. The content of the LDS additive is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and may be 18 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more relative to 100 parts by mass of the polycarbonate resin. By making it equal to or more than the lower limit, the plating property is more effectively exhibited. In particular, by making it equal to or more than 30 parts by mass, both the high dielectric constant and the low dielectric loss tangent tend to be well balanced and improved. In addition, the content of the LDS additive is preferably equal to or less than 120 parts by mass, more preferably equal to or less than 100 parts by mass, even more preferably equal to or less than 80 parts by mass, even more preferably equal to or less than 70 parts by mass, and even more preferably equal to or less than 69 parts by mass. By making it equal to or less than the upper limit, it is possible to further lower the dielectric loss tangent. The resin composition of the present invention may contain only one type of LDS additive, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0067] <Inorganic fillers> The resin composition of the present invention may contain an inorganic filler, and preferably contains an inorganic filler. The inorganic filler in the present invention does not include those corresponding to LDS additives. When an inorganic filler is contained, the strength and rigidity of the obtained molded product can be increased. On the other hand, when an inorganic filler is blended, the dielectric tangent generally tends to be high. However, in the present invention, by using a polycarbonate resin containing a certain amount of the constitutional unit represented by formula (1), a low dielectric tangent can be achieved even when an inorganic filler is blended.

[0068] The inorganic filler refers to a filler that is added to a resin component to improve strength and / or rigidity, and may be in any form such as fibrous, plate-like, granular, or amorphous, but is preferably in a fibrous or plate-like form. By using a fibrous or plate-like inorganic filler, a molded product can be obtained with a relatively small amount of the filler. In particular, by using a fibrous inorganic filler, a molded product can be obtained with a relatively small amount of the filler. The inorganic filler used in the present invention preferably has a raw material aspect ratio (aspect ratio before melt kneading) of 2 or more, more preferably 3 or more, and may further be 20 or more, 100 or more, 150 or more, or 200 or more. The upper limit of the aspect ratio is, for example, 400 or less, preferably 350 or less, more preferably 300 or less, and may further be 260 or less. The inorganic filler used in the present invention preferably has an aspect ratio in the pellet or molded product of 2 or more, more preferably 3 or more, and may be 5 or more, or 8 or more. The upper limit of the aspect ratio is, for example, 100 or less, preferably 60 or less, preferably 50 or less, and may be 40 or less. The aspect ratio is the number average value of the aspect ratios of 100 arbitrary inorganic fillers. More specifically, the aspect ratio is calculated from the measured values ​​obtained by randomly extracting the target inorganic filler from an image obtained by observation with an optical microscope, measuring its length, and then calculating the aspect ratio. The observation is performed at a magnification of 20 times. The same applies to the number average length and the like described later.

[0069] When the inorganic filler is in the form of fibers, examples thereof include glass fibers, carbon fibers, silica-alumina fibers, zirconia fibers, boron fibers, boron nitride fibers, potassium silicon nitride titanate fibers, metal fibers, wollastonite, etc. When the inorganic filler is in the form of fibers, glass fibers and wollastonite are preferred, and glass fibers are more preferred.

[0070] When the inorganic filler is fibrous, the cross section of the fiber may be any shape, such as circular, elliptical, oval, rectangular, a shape in which both short sides of a rectangle are joined to a semicircle, cocoon-shaped, etc., but a circular shape is preferred. Here, the circular shape includes not only a circular shape in the mathematical sense, but also a shape that is usually called a circular shape in the technical field of the present invention. When the inorganic filler is fibrous, the number average fiber length of the fibers is preferably 0.1 to 10 mm, more preferably 1 to 5 mm. By using fibers with such a number average fiber length, the mechanical strength can be further improved. In addition, the lower limit of the number average fiber diameter of the fibers is preferably 4.0 μm or more, more preferably 4.5 μm or more, and even more preferably 5.0 μm or more. The upper limit of the number average fiber diameter of the fibers is preferably 15.0 μm or less, more preferably 14.0 μm or less, and may be 12.0 μm or less. By using fibers having a number average fiber diameter in such a range, a resin molded product with excellent plating properties can be obtained even after wet heat treatment. Furthermore, even when the resin molded product is stored for a long period of time or heat treated for a long period of time, high plating properties can be maintained.

[0071] The fibrous inorganic filler is preferably glass fiber, and the glass fiber is obtained by melt spinning commonly supplied glasses such as E glass (electrical glass), C glass (chemical glass), A glass (alkaline glass), S glass (high strength glass), and alkali-resistant glass, but any glass fiber that can be made into glass fiber can be used without any particular limitation. In the present invention, the glass fiber preferably contains E glass.

[0072] The glass fiber used in the present invention is preferably surface-treated with a surface treatment agent such as a silane coupling agent, for example, γ-methacryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, etc. The amount of the surface treatment agent attached is preferably 0.01 to 1 mass% of the glass fiber. Furthermore, if necessary, it is also possible to use a glass fiber that has been surface-treated with a lubricant such as a fatty acid amide compound or silicone oil, an antistatic agent such as a quaternary ammonium salt, a resin having a film-forming ability such as an epoxy resin or urethane resin, or a mixture of a resin having a film-forming ability with a heat stabilizer, a flame retardant, etc.

[0073] Glass fibers are commercially available, such as T-187, T-571, T-595, T-286H, T-756H, and T-289H manufactured by Nippon Electric Glass Co., Ltd., DEFT2A manufactured by Owens Corning, HP3540 manufactured by PPG, and CSG3PA820 manufactured by Nitto Boseki Co., Ltd.

[0074] When the inorganic filler has a form other than fibrous, it is preferably in the form of a plate, granule or amorphous, more preferably in the form of a plate. The plate-like inorganic filler exhibits the function of reducing anisotropy and warpage, and examples of the plate-like inorganic filler include glass flakes, talc, mica, kaolin, boron nitride, metal foil, etc. Among the plate-like inorganic fillers, talc and boron nitride are preferred. The glass flakes preferably have a number average thickness of 0.5 to 20 μm and a number average length of 0.05 to 1.0 mm.

[0075] Other granular or amorphous inorganic fillers include ceramic beads, glass beads, asbestos, clay, zeolite, potassium titanate, barium sulfate, titanium oxide, silicon oxide, aluminum oxide, magnesium hydroxide, etc. Among these, titanium oxide is preferred. The glass beads preferably have a number average diameter of 5 to 100 μm.

[0076] In a preferred embodiment of the inorganic filler in the present invention, 90% by mass or more (more preferably 95% by mass or more, even more preferably 97% by mass or more, and even more preferably 99% by mass or more) is at least one type selected from the group consisting of glass, talc, wollastonite, titanium oxide, and boron nitride, preferably at least one type selected from the group consisting of glass, talc, and wollastonite, and more preferably glass. In particular, in the embodiment of the inorganic filler, the LDS additive contains at least two of the above-mentioned metals and has a resistivity of 5×10 3 By using a conductive oxide with a resistance of Ω·cm or less, a low dielectric tangent can be achieved more effectively.

[0077] In addition to the above, the inorganic filler can be described in paragraphs 0029 to 0031 of JP 2019-172712 A and in paragraphs 0075 to 0079 of JP 2017-110180 A, the contents of which are incorporated herein by reference.

[0078] The content of the inorganic filler (preferably the total content of at least one selected from the group consisting of glass fiber, talc, and boron nitride, more preferably the content of glass fiber) is preferably 10 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the polycarbonate resin. By making it equal to or more than the lower limit, the rigidity of the obtained electronic and electrical device parts can be further improved. On the other hand, by making it equal to or less than the upper limit, the processability during production tends to be further improved. The lower limit of the content of the inorganic filler can be adjusted depending on the application, and may be, for example, 15 parts by mass or more relative to 100 parts by mass of the polycarbonate resin. The upper limit of the content of the inorganic filler is preferably 80 parts by mass or less, more preferably 60 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin.

[0079] In addition, in the resin composition of the present invention, the mass ratio of the structural unit represented by formula (1) in the polycarbonate resin relative to 100 parts by mass of the inorganic filler is preferably 150 parts by mass or more. By making it 150 parts by mass or more, it is possible to maintain a high rigidity while maintaining a low dielectric tangent. The mass ratio of the structural unit represented by formula (1) in the polycarbonate resin relative to 100 parts by mass of the inorganic filler is more preferably 100 parts by mass or more, even more preferably 150 parts by mass or more, even more preferably 200 parts by mass or more, even more preferably 300 parts by mass or more, and even more preferably 500 parts by mass or more. In addition, the upper limit of the mass ratio of the structural unit represented by formula (1) in the polycarbonate resin relative to 100 parts by mass of the inorganic filler is more preferably 200 parts by mass or less, even more preferably 1500 parts by mass or less, even more preferably 1000 parts by mass or less, even more preferably 800 parts by mass or less, and even more preferably 600 parts by mass or less. By making the content equal to or less than the upper limit, both the rigidity and heat resistance required for electronic and electric device parts tend to be improved in a well-balanced manner.

[0080] The resin composition of the present invention may contain only one type of inorganic filler, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0081] In the resin composition of the present invention, the mass ratio of the inorganic filler to the LDS additive is usually 1:10 to 10:1, preferably 1:8 to 8:1, and more preferably 1:6 to 6:1. By setting the mass ratio in the above range, the strength and LDS performance required, particularly for electronic and electrical device parts, can be more effectively exhibited in a well-balanced manner.

[0082] <Other ingredients> The resin composition of the present invention may contain other components than those described above, if necessary, so long as the desired physical properties are not significantly impaired. Examples of other components include thermoplastic resins other than polycarbonate resins and various resin additives. Examples of thermoplastic resins other than polycarbonate resins include impact resistance improvers, styrene-based resins other than impact resistance improvers, and polyester resins. Examples of resin additives include dyes, heat stabilizers, antioxidants, release agents, UV absorbers, antistatic agents, flame retardants, flame retardant assistants, antifogging agents, lubricants, antiblocking agents, flow improvers, plasticizers, dispersants, antibacterial agents, etc. The resin additives may be contained alone or in any combination and ratio of two or more kinds.

[0083] <<Impact resistance improver>> The resin composition of the present invention preferably contains an impact modifier. The impact modifier is preferably an elastomer, and the elastomer is preferably a graft copolymer obtained by graft copolymerizing a rubber component with a monomer component copolymerizable therewith. The graft copolymer may be produced by any method such as bulk polymerization, solution polymerization, suspension polymerization, or emulsion polymerization, and the copolymerization method may be either one-stage grafting or multi-stage grafting.

[0084] The rubber component usually has a glass transition temperature of 0°C or lower, preferably -20°C or lower, and more preferably -30°C or lower. Specific examples of the rubber component include polybutadiene rubber, polyisoprene rubber, polyalkyl acrylate rubber such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymer, silicone rubber such as polyorganosiloxane rubber, butadiene-acrylic composite rubber, IPN (Interpenetrating Polymer Network) type composite rubber consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, styrene-butadiene rubber, ethylene-α-olefin rubber such as ethylene-propylene rubber, ethylene-butene rubber, and ethylene-octene rubber, ethylene-acrylic rubber, and fluororubber. These may be used alone or in combination of two or more. Among these, polybutadiene rubber, polyalkyl acrylate rubber, polyorganosiloxane rubber, IPN type composite rubber consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, and styrene-butadiene rubber are preferred from the standpoint of mechanical properties and surface appearance.

[0085] Specific examples of the monomer component that can be graft-copolymerized with the rubber component include aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride, etc.). These monomer components may be used alone or in combination of two or more. Among these, from the standpoint of mechanical properties and surface appearance, aromatic vinyl compounds, vinyl cyanide compounds, (meth)acrylic acid ester compounds, and (meth)acrylic acid compounds are preferred, and (meth)acrylic acid ester compounds are more preferred. Specific examples of the (meth)acrylic acid ester compounds include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and octyl (meth)acrylate.

[0086] The graft copolymer obtained by copolymerizing a rubber component is preferably a core / shell type graft copolymer in terms of impact resistance and surface appearance. Among them, a core / shell type graft copolymer is particularly preferred, which is composed of a core layer made of at least one rubber component selected from polybutadiene-containing rubber, polybutyl acrylate-containing rubber, polyorganosiloxane rubber, and an IPN type composite rubber made of polyorganosiloxane rubber and polyalkyl acrylate rubber, and a shell layer formed by copolymerizing (meth)acrylic acid ester around the core layer. The above-mentioned core / shell type graft copolymer preferably contains 40% by mass or more (preferably 90% by mass or less) of a rubber component (preferably butadiene rubber), more preferably 60% by mass or more (preferably 85% by mass or less). In addition, it is preferable that the (meth)acrylic acid is contained in an amount of 10% by mass or more (preferably 60% by mass or less), more preferably 15% by mass or more (preferably 40% by mass or less). Here, the core / shell type does not necessarily mean that the core layer and the shell layer are clearly distinguishable, but is intended to broadly include compounds obtained by graft polymerizing a rubber component around a core portion.

[0087] Preferred specific examples of these core / shell type graft copolymers include butadiene-methyl acrylate copolymer, methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-butadiene copolymer, methyl methacrylate-acrylic / butadiene rubber copolymer, methyl methacrylate-acrylic / butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic / silicone IPN rubber) copolymer, etc. Such rubbery polymers may be used alone or in combination of two or more.

[0088] When the resin composition of the present invention contains an impact modifier, the content of the impact modifier is preferably 2 parts by mass or more, more preferably 4 parts by mass or more, and even more preferably 6 parts by mass or more, based on 100 parts by mass of the polycarbonate resin in total. By making the content of the impact modifier 2 parts by mass or more, the impact resistance tends to be further improved. In addition, the content of the impact modifier is preferably 20 parts by mass or less, more preferably 18 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the polycarbonate resin in total. By making the content of the impact modifier 20 parts by mass or less, the flowability tends to be further improved. The impact resistance improver may be contained in only one type, or in two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0089] <<Heat stabilizer>> As the heat stabilizer, a phosphorus-based stabilizer is preferably used. Any known phosphorus stabilizer can be used. Specific examples include phosphorus oxoacids such as phosphoric acid, phosphonic acid, phosphorous acid, phosphinic acid, and polyphosphoric acid; metal acid pyrophosphates such as sodium acid pyrophosphate, potassium acid pyrophosphate, and calcium acid pyrophosphate; phosphates of Group 1 or Group 2B metals such as potassium phosphate, sodium phosphate, cesium phosphate, and zinc phosphate; organic phosphate compounds, organic phosphite compounds, and organic phosphonite compounds, with organic phosphite compounds being particularly preferred.

[0090] Examples of organic phosphite compounds include triphenyl phosphite, tris(mononylphenyl)phosphite, tris(mononyl / dinonyl phenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, monooctyl diphenyl phosphite, dioctyl monophenyl phosphite, monodecyl diphenyl phosphite, didecyl monophenyl phosphite, tridecyl phosphite, trilauryl phosphite, tristearyl phosphite, and 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite. Specific examples of such organic phosphite compounds include "ADK STAB (registered trademark; the same applies below) 1178," "ADK STAB 2112," "ADK STAB HP-10," and "AX-71" manufactured by ADEKA Corporation; "JP-351," "JP-360," and "JP-3CP" manufactured by Johoku Chemical Industry Co., Ltd.; and "IRGAFOS (registered trademark; the same applies below) 168" manufactured by BASF.

[0091] The content of the heat stabilizer in the resin composition of the present invention is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.3 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin. By setting the content of the heat stabilizer within the above range, the effect of adding the heat stabilizer is more effectively exhibited. The resin composition of the present invention may contain only one type of heat stabilizer, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0092] <<Antioxidants>> As the antioxidant, a phenol-based antioxidant is preferable, and a hindered phenol-based antioxidant is more preferable. Specific examples of hindered phenol-based antioxidants include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide], 2,4-dimethyl-6-(1-methylpentadecyl)phenol, diethyl[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesityl 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl) 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, and the like.

[0093] Among them, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate are preferred. Specific examples of such hindered phenol stabilizers include "Irganox (registered trademark, the same applies below) 1010" and "Irganox 1076" manufactured by BASF, and "Adeka STAB AO-50" and "Adeka STAB AO-60" manufactured by ADEKA.

[0094] The content of the antioxidant in the resin composition of the present invention is usually 0.001 parts by mass or more, preferably 0.005 parts by mass or more, more preferably 0.01 parts by mass or more, and usually 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, relative to 100 parts by mass of the polycarbonate resin. By setting the content of the antioxidant within the above range, the effect of adding the antioxidant is more effectively exhibited. The resin composition of the present invention may contain only one type of antioxidant, or may contain two or more types. When two or more types are contained, the total amount is preferably within the above range.

[0095] <<Release agent>> Examples of the release agent include aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, and polysiloxane-based silicone oils.

[0096] Examples of the aliphatic carboxylic acid include saturated or unsaturated aliphatic mono-, di- or tri-carboxylic acids. Here, the aliphatic carboxylic acid also includes alicyclic carboxylic acids. Among these, preferred aliphatic carboxylic acids are mono- or di-carboxylic acids having 6 to 36 carbon atoms, and more preferred are saturated aliphatic mono-carboxylic acids having 6 to 36 carbon atoms. Specific examples of such aliphatic carboxylic acids include palmitic acid, stearic acid, caproic acid, capric acid, lauric acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, melissic acid, tetralinic acid, montanic acid, adipic acid, and azelaic acid.

[0097] The aliphatic carboxylic acid in the ester of an aliphatic carboxylic acid and an alcohol can be, for example, the same as the aliphatic carboxylic acid. On the other hand, the alcohol can be, for example, a saturated or unsaturated monohydric or polyhydric alcohol. These alcohols may have a substituent such as a fluorine atom or an aryl group. Among these, a monohydric or polyhydric saturated alcohol having 30 or less carbon atoms is preferred, and an aliphatic saturated monohydric alcohol or an aliphatic saturated polyhydric alcohol having 30 or less carbon atoms is more preferred. Here, the term "aliphatic" also includes alicyclic compounds.

[0098] Specific examples of such alcohols include octanol, decanol, dodecanol, stearyl alcohol, behenyl alcohol, ethylene glycol, diethylene glycol, glycerin, pentaerythritol, 2,2-dihydroxyperfluoropropanol, neopentylene glycol, ditrimethylolpropane, and dipentaerythritol.

[0099] The above ester may contain aliphatic carboxylic acid and / or alcohol as impurities. The above ester may be a pure substance, or may be a mixture of a plurality of compounds. The aliphatic carboxylic acid and alcohol that are combined to form an ester may each be used alone or in any combination and ratio of two or more.

[0100] Specific examples of esters of aliphatic carboxylic acids and alcohols include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate (stearic acid stearate), behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, and the like.

[0101] In addition to the above, the ester compounds described in paragraphs 0029 to 0073 of WO 2019 / 078162 can be used as the release agent, the contents of which are incorporated herein by reference.

[0102] The content of the release agent in the resin composition of the present invention is usually 0.001 parts by mass or more, preferably 0.01 parts by mass or more, and usually 2 parts by mass or less, preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, based on 100 parts by mass of the total of the polycarbonate resin component and other resin components blended as necessary. By making the content of the release agent equal to or more than the lower limit of the above range, the effect of releasability is effectively exhibited, and by making it equal to or less than the upper limit of the above range, the decrease in hydrolysis resistance and mold contamination during injection molding can be more effectively suppressed. Regardless of the content of the release agent, a molded product with excellent transparency can be obtained, but by making it equal to or less than the upper limit of the above range, hardness and heat resistance tend to be further improved. The release agent may be contained in only one type, or in two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0103] <<Ultraviolet absorber>> For information on ultraviolet absorbents, refer to paragraphs 0059 to 0062 of JP2016-216534A, the contents of which are incorporated herein by reference.

[0104] <<Antistatic agent>> For information on the antistatic agent, refer to paragraphs 0063 to 0067 of JP2016-216534A, the contents of which are incorporated herein by reference.

[0105] <<Flame retardants>> For flame retardants, the descriptions in paragraphs 0068 to 0075 of JP2016-216534A can be referred to, the contents of which are incorporated herein by reference.

[0106] <Characteristics of resin composition> Next, preferred characteristics of the resin composition of the present invention will be described. The resin composition of the present invention, when molded into a flat plate, can have a pencil hardness of H or more, and can also have a pencil hardness of 2H or more, or 3H or more, as measured according to JIS K5600. The upper limit of the pencil hardness is not particularly specified, but for example, a pencil hardness of 4H or less sufficiently satisfies the required performance. In the present invention, the use of a polycarbonate resin containing a structural unit represented by formula (1) can improve scratch resistance. The resin composition of the present invention, when molded into a flat plate, can have a dielectric loss tangent at a frequency of 2.45 GHz of 0.0200 or less, and can also have a dielectric loss tangent at a frequency of 0.0150 or less, or 0.010 or less. The lower limit of the dielectric loss tangent at a frequency of 2.45 GHz is not particularly specified, but 0.0010 or more is practical. In the present invention, the dielectric loss tangent can be reduced by using a polycarbonate resin containing a structural unit represented by formula (1). The resin composition of the present invention can have a flexural modulus of 2500 MPa or more, and can also have a flexural modulus of 3000 MPa or more when molded into an ISO multipurpose test piece (4 mm thick). The upper limit of the flexural modulus is practically 13000 MPa or less. The resin composition of the present invention, when molded into an ISO multipurpose test piece (4 mm thick), can have a bending strength of 80 MPa or more, and can also have a bending strength of 90 MPa or more. The upper limit of the bending elastic modulus is practically 200 MPa or less.

[0107] <Method of producing resin composition> There is no limitation on the method for producing the resin composition of the present invention, and a wide variety of known methods for producing resin compositions can be used. Examples of such methods include a method in which the polycarbonate resin and other components that are blended as necessary are premixed using various mixers such as a tumbler or a Henschel mixer, and then melt-kneaded using a mixer such as a Banbury mixer, a roll, a Brabender, a single-screw kneading extruder, a twin-screw kneading extruder, or a kneader. The melt-kneading temperature is not particularly limited, but is usually in the range of 240 to 320°C.

[0108] <Molded products> The above-mentioned resin composition (for example, pellets) can be molded into a molded article by various molding methods. That is, the molded article of the present invention is molded from the resin composition of the present invention. The shape of the molded article is not particularly limited and can be appropriately selected depending on the use and purpose of the molded article, and examples thereof include film-like, rod-like, cylindrical, annular, circular, elliptical, polygonal, irregularly shaped, hollow, frame-like, box-like, panel-like, button-like, etc. Among these, film-like, frame-like, panel-like, and button-like shapes are preferred, and the thickness is, for example, about 1 mm to 5 mm in the case of the frame-like and panel-like shapes.

[0109] The method for forming the molded article is not particularly limited, and a conventionally known molding method can be adopted, for example, injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding) molding, rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, pressure molding, etc. In particular, the resin composition of the present invention is suitable for molded articles obtained by injection molding, injection compression molding, and extrusion molding. However, it goes without saying that the resin composition of the present invention is not limited to molded articles obtained by these methods.

[0110] The resin composition of the present invention is used in electronic and electrical equipment parts that use electromagnetic waves with a frequency of 1 GHz or more. The electronic and electrical equipment parts may be at least partially passed by electromagnetic waves with a frequency of 1 GHz or more. Here, the electronic and electrical equipment parts of the present invention can be used in a wide range of frequency bands of 1 GHz or more, but are generally preferably used in a frequency band of 1 to 20 GHz, particularly 1 to 10 GHz, and further preferably 1 to 3 GHz. More specifically, the electronic and electrical device parts in the present invention include housings for electronic and electrical devices, circuit boards, semiconductor interlayer insulating films, antenna parts, insulating materials for high-frequency coaxial cables, resistors, switches, capacitors, base parts such as photosensors, IC sockets and connectors, transportation equipment such as automobiles, bicycles, motorcycles, trucks, railroad cars, helicopters, and aircraft, construction machinery such as bulldozers, hydraulic excavators, and cranes, ships such as merchant ships, special-purpose ships, fishing boats, and naval vessels, agricultural machinery such as tractors and harvesters, mechanical parts such as smartphones, tablets, wearable devices, computers, television receivers, VR goggles, cameras, speakers, drones, robots, sensors, medical equipment, and analytical equipment, and are particularly preferably used as housings for electronic and electrical devices.

[0111] The molded article obtained by molding the resin composition of the present invention is preferably used as a molded article (plated molded article) having a plating on the surface of the molded article. The plating in the molded article of the present invention is preferably in an embodiment having antenna performance.

[0112] <Method of manufacturing plated molded products> Next, a method for producing a plated molded article will be disclosed, which comprises irradiating a laser onto the surface of a molded article formed from the resin composition of the present invention, and then applying a metal to form a plating. Fig. 1 is a schematic diagram showing a process of forming a plating on the surface of a molded article 1 by laser direct structuring technology. In Fig. 1, the molded article 1 is a flat substrate, but it does not necessarily have to be a flat substrate and may be a molded article that is partially or entirely curved. In addition, the obtained plated molded article is not limited to a final product, but also includes various parts. The first embodiment of the molded product has a smooth surface. Conventional plating is performed by filing the surface of a molded product made of resin to provide irregularities on the surface in order to improve adhesion with the plating, but in the present invention, plating can be formed even on a smooth flat surface. The second embodiment of the molded product is an embodiment in which the portion on which plating is to be formed on the molded product is not a uniform flat surface. Specifically, it is a molded product having convex portions and / or concave portions. In the present invention, since the range of laser conditions is wide, plating can be appropriately formed on molded products in which the portion on which plating is to be formed is not a uniform flat surface.

[0113] Returning to FIG. 1 again, the molded article 1 is irradiated with a laser 2. The laser here is not particularly limited and can be appropriately selected from known lasers such as a YAG laser, an excimer laser, and an electromagnetic ray, with a YAG laser being preferred. The wavelength of the laser is also not particularly limited. A preferred wavelength range is 200 nm to 1200 nm, and more preferably 800 to 1200 nm. When the laser is irradiated, the molded article 1 is activated only at the portion 3 irradiated with the laser. In this activated state, a plating solution 4 is applied to the molded article 1. The plating solution 4 is not particularly specified, and a wide variety of known plating solutions can be used. A plating solution (particularly, an electroless plating solution) containing at least one of copper, nickel, silver, gold, and palladium as a metal component is preferable, a plating solution (particularly, an electroless plating solution) containing at least one of copper, nickel, silver, and gold is more preferable, and a plating solution (particularly, an electroless plating solution) containing copper is even more preferable. That is, in the plating of the present invention, the metal component is preferably at least one of the above metals. There is no particular restriction on the method for applying the plating liquid 4 to the molded article 1, but an example is a method in which the molded article is immersed in a liquid containing a plating liquid. After the plating liquid is applied to the molded article, plating 5 is formed only on the portions irradiated with the laser. In the method of the present invention, it is possible to form a plating (circuit) having a gap of 1 mm or less, or even 150 μm or less (the lower limit is not particularly specified, but for example, 30 μm or more). In order to prevent corrosion or deterioration of the formed plating (circuit), the plating can be further protected with nickel or gold, for example, after electroless plating. Similarly, it is also possible to form a required film thickness in a short time by using electrolytic plating after electroless plating. In addition, the method for manufacturing the plated molded article is preferably used as a method for manufacturing a component of a portable electronic device having an antenna, including the method for manufacturing the plated molded article.

[0114] In addition, without departing from the spirit of the present invention, the descriptions in JP-A-2011-219620, JP-A-2011-195820, JP-A-2011-178873, JP-A-2011-168705, and JP-A-2011-148267 can be referred to.

Examples

[0115] The present invention will be described more specifically with reference to the following examples. The materials, amounts used, ratios, treatment details, treatment procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below.

[0116] 1. Raw materials The materials shown in Table 1 below were used.

Table 1

[0117] <Synthesis example of C-PC> 100 mol% of 2,2-bis(4-hydroxy-3-methylphenyl)propane, 103 mol% of diphenyl carbonate (DPC), and 1.5×10 -6 mol% of cesium carbonate as a catalyst were precisely weighed to prepare a mixture. Next, the mixture was charged into a 200 L first reactor equipped with a stirrer, a heat medium jacket, a vacuum pump, and a reflux condenser. Next, the inside of the first reactor was depressurized to 1.33 kPa (10 Torr), and then the operation of returning the pressure to atmospheric pressure with nitrogen was repeated five times, and the inside of the first reactor was replaced with nitrogen. After the nitrogen replacement, the inside temperature of the first reactor was gradually increased by passing a heat medium at a temperature of 230 ° C through the heat medium jacket, and the mixture was dissolved. Then, the stirrer was rotated at 55 rpm, and the temperature in the heat medium jacket was controlled to keep the inside temperature of the first reactor at 220 ° C. Then, while distilling off the phenol by-produced by the oligomerization reaction of the aromatic dihydroxy compound and DPC carried out inside the first reactor, the pressure in the first reactor was reduced from 101.3 kPa (760 Torr) to 13.3 kPa (100 Torr) in absolute pressure over 40 minutes. Next, the pressure in the first reactor was maintained at 13.3 kPa, and the transesterification reaction was carried out for 80 minutes while further distilling off the phenol. Thereafter, the system was restored to an absolute pressure of 101.3 kPa with nitrogen, and then the gauge pressure was increased to 0.2 MPa, and the oligomer in the first reactor was pumped to the second reactor via a transfer pipe preheated to 200° C. or higher. The second reactor had an internal volume of 200 L and was equipped with a stirrer, a heat medium jacket, a vacuum pump, and a reflux condenser, and the internal pressure was controlled to atmospheric pressure and the internal temperature to 240° C. Next, the oligomer pumped into the second reactor was stirred at 16 rpm, the internal temperature was raised by a heat medium jacket, and the pressure in the second reactor was reduced from 101.3 kPa to 13.3 kPa in absolute pressure over 40 minutes. After that, the temperature was continued to be raised, and the internal pressure was reduced from 13.3 kPa to 399 Pa (3 Torr) in absolute pressure over another 40 minutes, and the distilled phenol was removed from the system. Furthermore, the temperature was continued to be raised, and after the absolute pressure in the second reactor reached 70 Pa (about 0.5 Torr), it was maintained at 70 Pa and the polycondensation reaction was carried out. The final internal temperature in the second reactor was 285 ° C. The polycondensation reaction was terminated when the agitator of the second reactor reached a predetermined stirring power. Next, the inside of the second reactor was restored to an absolute pressure of 101.3 kPa with nitrogen, and then the gauge pressure was increased to 0.2 MPa. An aromatic polycarbonate resin was extracted in the form of strands from the bottom of the second reactor, and pelletized using a rotary cutter while being cooled in a water tank. The obtained pellets were blended with 4 times the molar amount of cesium carbonate butyl p-toluenesulfonate, fed into a twin-screw extruder, extruded into strands through the extruder die, and cut with a cutter to obtain aromatic polycarbonate resin (C-PC) with the polymerization catalyst deactivated.

[0118] <Measurement of viscosity average molecular weight (Mv) of polycarbonate resin> The viscosity average molecular weight (Mv) of the polycarbonate resin was calculated from the intrinsic viscosity (η) (unit: dL / g) at 20°C using an Ubbelohde viscometer with methylene chloride as a solvent, and the viscosity average molecular weight (Mv) was calculated from the following Schnell viscosity formula. η = 1.23 × 10 -4 Mv 0.83

[0119] <Proportion of Formula (1) (mass ratio of the structural unit represented by Formula (1) in the polycarbonate resin)> The mass ratio of the constitutional unit represented by formula (1) in the polycarbonate resin was calculated from the mixing ratio of the resin, the molecular weight of the molecule constituting the constitutional unit represented by formula (1), and the viscosity average molecular weight.

[0120] 2. Examples 1 to 12, Comparative Examples 1 to 6 <Production of Resin Composition Pellets> The components (except glass fiber) shown in Table 1 above were blended in the ratios (all parts by mass) shown in Table 2 or Table 3 below, and mixed uniformly in a tumbler mixer for 20 minutes. The mixture was then fed into the extruder from the barrel upstream of the extruder (Toshiba Machine Co., Ltd., TEM26SX) at a cylinder setting temperature of 280°C, a screw rotation speed of 250 rpm, and a discharge rate of 20 kg / hr, and melt-kneaded. Glass fiber was fed into the twin-screw extruder from a side feeder. After melt-kneading, the molten resin composition extruded in a strand shape was quenched in a cooling water tank and pelletized using a pelletizer to obtain pellets.

[0121] <Flexural modulus and flexural strength> The pellets obtained above were dried at 100°C for 5 hours, and then injection molded using an injection molding machine (NEX80) manufactured by Nissei Plastic Industrial Co., Ltd. under conditions of a cylinder temperature of 280°C, a mold temperature of 80°C, and a molding cycle of 50 seconds to produce ISO multipurpose test pieces (4 mm thick). The obtained test pieces were subjected to a bending test based on the ISO-178 standard at room temperature (23°C) to measure the bending modulus (unit: MPa) and bending strength (unit: MPa).

[0122] <Dielectric tangent> The dielectric loss tangent was measured at a frequency of 2.45 GHz by a perturbation method using a flat plate-shaped test piece of 100 mm×1.5 mm×2 mm formed from the resin composition. Specifically, the pellets obtained above were pre-dried at 100°C for 6 hours using a hot air dryer, and then injection molded using an injection molding machine (NEX80) manufactured by Nissei Plastic Industrial Co., Ltd. under conditions of a cylinder temperature of 280°C, a mold temperature of 80°C, and a molding cycle of 50 seconds to mold a flat test piece of 100 mm x 100 mm x 2 mm. A flat test piece of 100 mm x 1.5 mm x 2 mm was obtained from the obtained flat test piece by cutting, and the dielectric loss tangent at a frequency of 2.45 GHz was measured by a perturbation method using a network analyzer manufactured by KEYSIGHT and a cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd. The results are shown in Table 2 or Table 3.

[0123] <Measurement of pencil hardness> The ISO multipurpose test piece (4 mm thick) obtained above was subjected to pencil hardness measurement under a load of 1 kg using a pencil hardness tester in accordance with JIS K5600 to determine the pencil hardness. The pencil hardness tester used was a product of Toyo Seiki Seisakusho Co., Ltd. The results are shown in Table 2 or Table 3.

[0124] <Plating ability> A 10x10mm area of ​​the ISO multipurpose test piece (4mm thick) obtained above was irradiated with a Trumpf VMc1 laser irradiation device (1064nm wavelength YAG laser maximum output 15W) at a power of 6W or 8W, a frequency of 60kHz or 80kHz, and a speed of 4m / s. The subsequent plating process was carried out in an electroless plating bath of Enthone ENPLATE LDS CU 400 PC at 48℃. Evaluation was performed as follows. The results are shown in Table 2 or Table 3. A: Plating was formed B: No plating was formed

[0125] [Table 2] [Table 3]

[0126] In Tables 2 and 3 above, the proportion of formula (1) means the mass ratio (mass %) of the structural unit represented by formula (1) in the polycarbonate resin contained in the resin composition. As is clear from the above results, the resin composition of the present invention was able to form a plating and reduce the dielectric loss tangent (Examples 1 to 12). Furthermore, the pencil hardness was also increased. In contrast, the compositions of the comparative examples were able to form a plating, but had high dielectric loss tangents (Comparative Examples 1 to 6). Furthermore, the pencil hardness was also low. [Explanation of symbols]

[0127] 1 Molded product 2. Laser 3. Laser irradiated area 4. Plating solution 5. Plating

Claims

1. Contains polycarbonate resin and laser direct structuring additives. The content of the laser direct structuring additive relative to 100 parts by mass of the polycarbonate resin is 30 parts by mass or more and 150 parts by mass or less, A resin composition for laser direct structuring, wherein 5% by mass or more of all structural units of the polycarbonate resin are structural units represented by formula (1). 【Chemistry 1】 (In formula (1), R 1 and R 2 are each independently a hydrogen atom or a methyl group; W 1 represents a single bond or a divalent group.

2. A composition comprising a polycarbonate resin and a laser direct structuring additive, The content of the laser direct structuring additive relative to 100 parts by mass of the polycarbonate resin is 18 parts by mass or more and 150 parts by mass or less, A resin composition for laser direct structuring, wherein 5% by mass or more of all structural units of the polycarbonate resin are structural units represented by formula (1). 【Chemistry 2】 In formula (1), R 1 and R 2 each independently represent a hydrogen atom or a methyl group, and W 1 represents a single bond or a divalent group.

3. The resin composition according to claim 1 or 2, comprising the laser direct structuring additive in an amount of 0.1 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the polycarbonate resin.

4. The resin composition according to claim 1 or 2, further comprising an inorganic filler in an amount of 10 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of the polycarbonate resin.

5. The resin composition according to claim 4, wherein a mass ratio of the structural unit represented by formula (1) in the polycarbonate resin relative to 100 parts by mass of the inorganic filler is 150 parts by mass or more.

6. The resin composition according to claim 4 or 5, wherein the inorganic filler comprises at least one selected from the group consisting of glass, talc, wollastonite, titanium oxide and boron nitride.

7. The resin composition according to any one of claims 4 to 6, wherein the inorganic filler comprises glass fiber.

8. The resin composition according to any one of claims 1 to 7, further comprising a structural unit represented by formula (5): 【Chemistry 3】 (In formula (5), W 2 represents a single bond or a divalent group.

9. a polycarbonate resin (A1) in which 90% by mass or more of all structural units are structural units represented by formula (1) and a polycarbonate resin (A2) in which 90% by mass or more of all structural units are structural units represented by formula (5), The resin composition according to claim 8, wherein 25 mass% or more of the polycarbonate resin contained in the resin composition is the polycarbonate resin (A1).

10. The resin composition according to claim 9, wherein the polycarbonate resin (A1) has a viscosity average molecular weight of 16,000 or more and 30,000 or less, and the polycarbonate resin (A2) has a viscosity average molecular weight of 16,000 or more and 35,000 or less.

11. The resin composition according to any one of claims 1 to 10, further comprising an impact resistance improver in an amount of 2 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the polycarbonate resin.

12. The resin composition according to any one of claims 1 to 11, wherein the resin composition has a pencil hardness of H or more when molded into a plate shape, as measured according to JIS K5600.

13. The resin composition according to any one of claims 1 to 12, wherein the resin composition has a dielectric loss tangent of 0.0200 or less at a frequency of 2.45 GHz when molded into a flat plate.

14. The laser direct structuring additive comprises copper chromium oxide, an oxide containing at least one of antimony and phosphorus and tin, and at least two metals, and has a resistivity of 5×10 3 The resin composition according to any one of claims 1 to 13, comprising at least one selected from the group consisting of conductive oxides having a resistivity of Ω·cm or less.

15. The laser direct structuring additive comprises at least two metals and has a resistivity of 5×10 3 The resin composition according to any one of claims 1 to 14, comprising at least one selected from the group consisting of conductive oxides having a resistivity of Ω·cm or less.

16. The resin composition according to any one of claims 1 to 15, wherein the proportion of the structural unit represented by formula (1) relative to all structural units of the polycarbonate resin is 30 to 60 mass%.

17. The resin composition according to any one of claims 1 to 16, which is for use in electronic and electrical equipment parts that use electromagnetic waves having a frequency of 1 GHz or more.

18. A molded article formed from the resin composition according to any one of claims 1 to 17.

19. The molded article according to claim 18, which is an electronic or electrical device part that uses electromagnetic waves having a frequency of 1 GHz or more.

20. The molded article according to claim 18 or 19, having a plating on the surface of the molded article.

21. The molded article according to claim 20, wherein the plating possesses antenna properties.

22. A method for producing a plated molded article, comprising: irradiating a surface of a molded article formed from the resin composition according to any one of claims 1 to 17 with a laser, and then applying a metal to form a plating.

Citation Information

Patent Citations

  • Polymer composition

    EP2354185A1

  • Copolycarbonate, copolycarbonate composition and production thereof

    JP1996183852A

  • Patterned conductor structures, in particular fine patterned conductor structures, arranged on a non-conductive carrier material and method for producing the same

    JP2000503817A

  • Conductor track structure and method for manufacturing the same

    JP2004534408A

  • Method of manufacturing polycarbonate resin molding

    JP2013018240A